Spotlight on VET : 2018 compilation - (:unkn) unknown (Publications Office of the European Union, 2019)
"While countries share goals and challenges, their VET systems are diverse, shaped by socioeconomic contexts and traditions. Information on VET’s main features, its role and status, are a prerequisite to understanding developments and learning from another country. This compilation addresses all those who need a quick overview of essential features of VET in Europe. Clarifying the place of VET in countries' overall education and training systems, it presents main accession and progression routes for learners; types and levels of qualifications they lead to; types of programmes, delivery modes, work-based learning ratio and duration. The approach and terminology used for the systems charts and descriptions aim for a balance between national and international readers’ understanding and for some comparisons between systems. This publication is a useful starting point for work by policy makers, social partners, experts and researchers. It provides orientation to a range of other actors involved in VET-related activities: VET providers, teachers and trainers; guidance, qualifications and validation staff; and other readers who want to familiarise themselves with VET systems across and beyond Europe." (Editor, BIBB-Doku)

Die Cedefop-Publikation bietet einen Überblick über die wesentlichen Merkmale der beruflichen Bildung in 28 Ländern der Europäischen Union sowie Island und Norwegen.
Titelzusatz auf dem Umschlag: Vocational education and trainings systems in Europe
Keywords: S System beruflicher Bildung; I 2.2 Europa; Berufsbildungssystem; Europa